Pengembangan dan Validasi Instrumen Pengukuran Efektivitas Tim di Usaha Mikro Kecil dan Menengah (UMKM) - Faradilla Iedliany; Arief Fahmie; Elisa Kusrini (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
In general, research on the development of teamwork-measuring instruments is associated with the corporate context. While in Indonesia, research in the context of small and medium enterprises is equally important. This study aimed to develop and validate an instrument for measuring team effectiveness in small and medium enterprises (SMEs). The development of this measuring instrument used the theory developed by Cantu (2007) which consists of six aspects, namely teamwork, decision making, leadership support, trust and respect, recognition and appreciation, and customer focus. Research respondents were 404 employees from thirteen SMEs situated in Yogyakarta, who were selected by using purposive sampling technique. EFA analysis resulted in KMO = .821, indicating a reduction of the aspects from six to three: decision making, leadership support, and trust. While from the CFA analysis were obtained the values of CMIN=116,566, probability .057, CMIN/DF=1.240, GFI= .932, RMSEA = .034 so that it could be concluded that the model have been appropriate to measure the effectiveness of teamwork in small and medium enterprises.